The Economic Impacts of Natural Resource Dependency in Gulf Countries - Aljarallah, Ruba Abdullah (International Journal of Energy Economics and Policy, 2020)
Natural resources serve as useful inputs and vital raw materials for domestic industries, which stimulate and secure sustained economic growth and development. However, the notion that the richness of natural resources can be translated into a curse rather than a blessing has long been an overarching topic of research for both academics and policymakers. Natural resources wealth has noticeable socioeconomic and political impacts that vary among resource-rich countries. Given the importance of the Gulf Countries and their dependency on income from natural resources, this study examines the economic impacts of natural resource dependency by taking per capita GDP and Total Factor Productivity as dependent variables. This study applied the Autoregressive Distributed Lag and Error Correction Model by using time-series data from 1984 to 2014. The results indicate that, in the long-run, dependency on natural resources has a positive impact on per capita GDP in Saudi Arabia and United Arab Emirates, but the relationship is insignificant in Kuwait. Then, it is found that natural resource dependency shows a positive impact on TFP in Saudi Arabia and a negative impact in Kuwait, while the relationship is insignificant in the case of United Arab Emirates. Keywords: Natural resource dependency; Institutional quality; Human capital; Total factor productivity; Per capita GDP JEL Classifications: B15; E02; E24; I25; O47; Q32; Q38 DOI: https://doi.org/10.32479/ijeep.9836